PERFORMAN REPRODUKSI DAN PRODUKSI TERNAK BABI PADA USAHA PETERNAKAN RAKYAT DI DUA LOKASI BERBEDA - I G., SURANJAYA; DEWANTARI, M.; PARIMARTHA, I K. W.; SUKANATA, I W.; ARIANA, I N. T. (Majalah Ilmiah Peternakan; Vol 21 No 2 (2018): Vol 21, No 2 (2018)DO - 10.24843/MIP.2018.v21.i02.p06, 2018)
The research was conducted in a survey of farmers on the pig farm business in the Kebek and Penginyahan village, Payangan-Gianyar. Purposive random sampling of 20 farmers in each location and explorative approach was conducted to describe the production and reproduction management applied. Data were analyzed descriptively and to study production and reproduction management between the two sites was Two Independent Sample T Test. The results showed the average productivity of pigs in Kebek and Penginyahan that is litter size: 9,50±1,65 vs 10,86±1,68 tail, annual litter size : 2,10±0,32 vs 2,29±0,49 times, weaning age: 29,00±2,11 vs 29,00±1,91 day, and the three variables were not significantly different (P>0,05). The average number of piglet weaned in Kebek and Penginyahan was 7.90±1,45 vs 9,43±1,99 head, weaning weight of piglet 7,20±1,69 vs 5,29±0.57 kg (P <0.05). The dry period and the age of culled of sow in Kebek is significantly higher than in Penginyahan (P<0.05). Whereas in fattening management, early age to fatten and length of maintenance is not different between the two locations (P>0,05), whereas the live and slaughtering weight in Kebek are significantly higher than those in Penginyahan that is 14.00±1,15 vs. 12.20±1,79 kg and 126,50±11,80 vs. 114±10,84 kg (P<0,05).